Water Quality Bandar Kayangan Lembah Sari Lake Pekanbaru City be Reviewed from Characteristics Physics-Chemical and Coefficient Saphrobic - Oktaviandora '; Adriman '; Nuraini El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A study on the water quality Bandar Kayangan Lembah Sari lake pekanbaru city was conducted from April 2013 to Juli 2013. This research aims to quality of water in the bandar kayangan lembah sari lake be Reviewed from Characteristics Physics-Chemical and Coefficient Saphrobic. There were three stations with 3. Samples were taken 3 times, once a week and they were analyzed in the Ecological Environment Water Management Laboratory Faculty, Riau University.Parameters measured were water temperature, turbidity, brightness, current speed, total suspended solid, ammonia, pH, DO, BOD5, nitrate, phosphate, and plankton. Results shown that there were 7 classes present, namely Cyanophyceae (3 genus), Chlorophyceae (10 genus), Bacillariophyceae (4 genus), Dinophyceae (1 genus), Euglenophyceae (2 genus), Rotifer (3 genus) and Ciliate (1 genus). Water quality parameters are as follows: temperature: 29-30 0C, turbidity: 12,6-14,3 NTU, brightness current speed : 2,1-2,8 cm/s, total suspended solid: 22-40 mg/l, ammonia: 0,05-0,20 mg/l, pH : 5-6, DO : 2,4-6,5 mg/l, BOD5 : 3-3,6 mg/l, nitrate: 0,02-0,04 mg/l and phosphate 0,014-0,16 mg/l. be Reviewed from Characteristics Physics-Chemical and Coefficient Saphrobic in the Bandar Kayangan Lembah Sari Lake in a state of being tainted by bad and coefficient saphrobic in ranged from (β – meso/oligosaphrobic phase) to - (α/β – mesosaphrobic phase).Keywords : Bandar Kayangan Lake, Water Quality, plankton’s Saphrobic Coefficent1) Student of the Fisheries and Marine Science Faculty Riau University2) Lecturers of the Fisheries and Marine Science Faculty Riau UniversityI. PENDAHULUANDanau Bandar Kayangan Lembah Sari merupakan salah satu tempat wisata Pekanbaru yang bernuansa alami yang berlokasi di Kecamatan Rumbai. Danau Bandar Kayangan adalah